Analysis of Experiential Tourism in the Wayang Kamasan Workshop at Kamasan Village Klungkung - Ni Luh Putu Intan Nirmalasari; Ni Luh Gde Sari Dewi Astuti; Ida Bagus Gde Sena Baskara (Penerbit Lafadz Jaya, 2026)
This study examines the implementation of experiential tourism in the Kamasan wayang workshop at Sanggar Wasundari, Kamasan Village, Klungkung, Bali. Tourism trends have shifted tourist preferences from passive sightseeing toward participatory and authentic cultural experiences. In this context, the Kamasan wayang workshop has the potential to become a form of creative tourism by involving tourists directly in traditional painting activities while introducing the cultural values of classical Kamasan art. This research aims to analyze the experiential tourism elements applied in the workshop and identify tourists’ experiences during the activity. The study employed a mixed methods approach with qualitative dominance. Data were collected through participatory observation, in-depth interviews, questionnaires, and documentation involving 14 tourist participants. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using the Miles and Huberman model. The findings indicate that the workshop possesses strong characteristics of experiential and creative tourism. Most dimensions achieved average scores above 4.00 on a Likert scale of 1–5. The highest score was found in the Active Participation dimension (4.57), indicating direct tourist involvement in the creative process. The Authenticity dimension also obtained a high score (4.52), showing that tourists perceived the workshop as an authentic cultural experience. However, the Escapism dimension received the lowest score (4.17), suggesting that emotional immersion and experiential design still require further development. Overall, the Kamasan wayang workshop demonstrates significant potential as a sustainable experiential cultural tourism product.